Mass email at university: current literature and tactics for future use. (2nd September 2019) - Dawkins, Roger
ABSTRACT: I am a lecturer with professional marketing experience, and this study was motivated by my dismay at university about what I have perceived as oversights in colleagues' typical use of mass email (emailing a single message to a large group of subscribers) for content delivery, in comparison to the communication strategies of major industries (for example, retail and public administration). I examine non-academic research about mass email best-practise, as implemented in industry communications; then I perform a systematic review of academic research on mass email for content delivery. My review of 19 studies confirms academics are behind the industry when it comes to mass email evaluation and optimisation strategies. Finally, I outline tactics necessary for more effective mass emails at university, the most salient being systematically analysing a range of email metrics, and testing and optimising emails. Also, included in this study is my identification of current obstacles to more effective mass email at university, and these include the technological limitations of learning management systems (LMS), and the limited expertise of teaching staff.